2012
DOI: 10.1016/j.cell.2012.11.054
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitor of Nonhomologous End-Joining Abrogates Double-Strand Break Repair and Impedes Cancer Progression

Abstract: DNA Ligase IV is responsible for sealing of double-strand breaks (DSBs) during nonhomologous end-joining (NHEJ). Inhibiting Ligase IV could result in amassing of DSBs, thereby serving as a strategy toward treatment of cancer. Here, we identify a molecule, SCR7 that inhibits joining of DSBs in cell-free repair system. SCR7 blocks Ligase IV-mediated joining by interfering with its DNA binding but not that of T4 DNA Ligase or Ligase I. SCR7 inhibits NHEJ in a Ligase IV-dependent manner within cells, and activates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
396
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(415 citation statements)
references
References 56 publications
17
396
0
1
Order By: Relevance
“…Three repair inhibitors were used: two of them modify NHEJ (NU7026 and SCR7) [39][40][41] and IR-1 disrupts HR (supplemental Materials and methods). 42 To investigate the effect of the combination treatment of melphalan with an inhibitor, we first selected the optimal concentrations of the inhibitors that, when administered alone, showed minimal decrease in cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Three repair inhibitors were used: two of them modify NHEJ (NU7026 and SCR7) [39][40][41] and IR-1 disrupts HR (supplemental Materials and methods). 42 To investigate the effect of the combination treatment of melphalan with an inhibitor, we first selected the optimal concentrations of the inhibitors that, when administered alone, showed minimal decrease in cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, Maruyama et al [14] have shown that the frequency of HDR is improved by microinjection of a DNA ligase IV inhibitor, SCR7, into mouse zygotes with sgRNA/ Cas9/ssODN [15]. Another way to improve the efficiency is enhancement of the HDR pathway.…”
Section: Hdr-mediated Production Of Nucleotide Substitution In Micementioning
confidence: 99%
“…2A and detailed in Methods), NHEJ proteins were incubated with linearized plasmid dsDNA, allowing assembly of NHEJ proteins on the DNA, facilitating NHEJ and formation of intermediates in that pathway. This reaction was performed in the absence or presence of the LigIV-specific inhibitor SCR7 (43). A cross-linking reagent [4% (wt/vol) paraformaldehyde (PFA)] was then added to the reactions to preserve structural intermediates.…”
Section: Sr Imagingmentioning
confidence: 99%